92 Religious and cultural factors: barriers to developing interventions and safety countermeasures. (1st September 2016) - Kayani, Ahsan; King, Mark; Fleiter, Judy
Abstract : Background: Most of the world's people live in developing countries yet there has been limited application of scientific methods of injury control in many of them. Traditional cultural and religious values can act as a barrier to health-promoting and injury prevention behaviours, in general and especially in relation to road safety, and may also contribute to risk-taking behaviours. Such beliefs, including fatalism and superstition, can present significant challenges for health advocates who aim to change behaviour in order to avert road crashes and diminish their consequences. Methods: Qualitative research was undertaken in Islamabad, Rawalpindi and Lahore in Pakistan with a range of drivers, religious orators, police and policy makers to explore cultural and religious beliefs and their association with risky road use, and to understand how they might affect development of road safety interventions. Results: Overall, findings indicated a variety of strongly-held religious and cultural beliefs (such as fatalism and superstition), many that were non-scientific in nature, about road crash causation and ways in which people protect against harm on the road. The findings highlight a range of issues, including the identification of aspects of beliefs that have complex social implications when designing safety intervention strategies. The pervasive nature of such beliefs can affect road user behaviour by reinforcing the presumption that the individual has no part to play in safety, thereby supporting continued risk taking behaviours. Conclusions: The mechanisms of culture and religion should be taken into account when trying to change attitudes and behaviours relating to public health. For effective road safety interventions in developing countries, it is important to understand the prevailing cultural and social beliefs towards road crashes which influence behaviour and thereby preventive measures and responses to interventions adapted from developed countries.